Tissue-specific effects of sulfonylureas: lessons from studies of cloned K(ATP) channels. - Ashcroft, F; Gribble, F (2000)
Sulfonylureas stimulate insulin secretion in type-2 diabetic patients by blocking ATP-sensitive (K(ATP)) potassium channels in the pancreatic beta-cell membrane. This effect is mediated by the binding of the drug to the sulfonylurea receptor (SUR) subunit of the channel. K(ATP) channels are also present in other tissues, but often contain different types of SUR subunits (e.g., SUR1 in beta-cells, SUR2A in heart, SUR2B in smooth muscle). The sensitivity of these different types of K(ATP) channels to sulfonylureas is variable: gliclazide and tolbutamide block the beta-cell, but not the cardiac or smooth muscle, types of K(ATP) channel. In contrast, glibenclamide blocks all three types of channel with similar affinity. The reversibility of the drugs also varies, with tolbutamide and gliclazide being reversible on all three types of K(ATP) channel, while glibenclamide is reversible on cardiac, but not beta-cell, K(ATP) channels. This review summarizes current knowledge of how sulfonylureas act on the different types of K(ATP) channel found in beta-cells and in extrapancreatic tissues, and discusses the implications of these findings for their use as therapeutic agents.